Improved blocking capability of N-ion-implanted β-Ga2O3 U-shaped trench gate MOSFET by annealing in oxygen - Qi Liu; Jingbo Zhou; Xuanze Zhou; Man Hoi Wong; Huidong Yao; Jinyang Liu; Xiaodong Zhang; Guangwei Xu; Shibing Long (Applied Physics Express)
To improve the blocking capability of U-shaped trench gate MOSFETs (UMOSFETs) based on nitrogen-implanted current blocking layer (CBL), the post-implantation annealing atmosphere is optimized. Compared to the UMOSFET annealed in nitrogen, the oxygen-annealed device shows an improved breakdown voltage, increasing from 830 V to 1330 V, while maintaining similar specific on-resistance. By analyzing the leakage mechanisms of CBLs, the lower leakage current in the oxygen-annealed device is attributed to the reduced concentration of certain deep donors and the change in trap energy level involved in the Poole–Frenkel (PF) emission. This work validates oxygen annealing as an effective approach to optimizing nitrogen-implanted β -Ga _2 O _3 power MOSFETs.